Transparency: A Necessary First Step toward an Ethic of Finance - Rothlin, Stephan; McCann, Dennis (Silliman Journal, 2022)
The demand for greater transparency is a hallmark of today’s efforts to promote international business ethics, especially in global financial markets. But what is transparency? Is it a moral absolute? If not, what are its limits? If it is a means, what ends must it serve? Is it possible to have too much as well as too little transparency, especially as it is institutionalized in financial markets? The following is an attempt to address these questions, in light of a particular case study, namely, the controversies surrounding Alibaba Group Holdings and its IPO applications first in Hong Kong (HKSE) and then in New York (NYSE). The authors conclude that, in promoting the Alibaba IPO and related ventures, Jack Ma asked for the trust of investors and other stakeholders, without achieving a robust transparency that would clearly warrant that trust. The authors are concerned to integrate legitimate demands for transparency into an ethic of finance that, while respecting Asian cultural values, also facilitates Asian business development internationally.